Converting NCL Documents to Smix and Fixing Their Semantics and Interpretation in the Process - Lima, Guilherme Augusto Ferreira; Azevedo, Roberto Gerson De Albuquerque; Colcher, Sérgio; Haeusler, Edward Hermann (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
In this paper, we present the conversion of NCL to Smix and discuss its main implications. NCL is a declarative language for the specification of interactive multimedia presentations which was adopted by the ITU-T H.761 recommendation for interoperable IPTV services. Smix is a synchronous domain-specific language with a similar purpose, but with a simpler and more precise semantics. By implementing NCL over Smix, we bring to the former the notions of reaction and execution instants, and with them some benefits. From a practical perspective, we fix the semantics of the converted documents, get a leaner NCL player (the Smix interpreter), and simplify further conversions. From a systems-design perspective, the structured conversion of NCL to Smix helps us tame the complexity of mapping the user-oriented constructs of NCL into the machine-oriented primitives that realize them as a multimedia presentation. In the paper, we present NCL and Smix, discuss related work on document conversion, and detail the conversion process and a prototype implementation.